1998
DOI: 10.1074/jbc.273.10.5685
|View full text |Cite
|
Sign up to set email alerts
|

Purification to Apparent Homogeneity and Properties of Pig Kidneyl-Fucose Kinase

Abstract: L-Fucokinase was purified to apparent homogeneity from pig kidney cytosol. The molecular mass of the enzyme on a gel filtration column was 440 kDa, whereas on SDS gels a single protein band of 110 kDa was observed. This 110-kDa protein was labeled in a concentration-dependent manner by azido-[ 32 P]ATP, and labeling was inhibited by cold ATP. The 110-kDa protein was subjected to endo-Lys-C digestion, and several peptides were sequenced. These showed very little similarity to other known protein sequences. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 14 publications
2
53
2
Order By: Relevance
“…As generalized hypofucosylation is a biochemical hallmark of cells derived from LAD II patients (1,20), we determined whether fucose incorporation into macromolecules was affected in cells obtained from this patient. EBVtransformed lymphoblasts were grown in the presence of [ 3 H]-fucose, which can be converted to GDP-L- [ 3 H]-fucose by the salvage pathway (29,30). As shown in Figure 1, A and B, whereas the amount of radiolabeled fucose bound to acidprecipitable macromolecules was comparable in control, mother, and father, incorporation into macromolecules in patient cells was severely impaired (20% of that observed in the other samples).…”
Section: Resultsmentioning
confidence: 99%
“…As generalized hypofucosylation is a biochemical hallmark of cells derived from LAD II patients (1,20), we determined whether fucose incorporation into macromolecules was affected in cells obtained from this patient. EBVtransformed lymphoblasts were grown in the presence of [ 3 H]-fucose, which can be converted to GDP-L- [ 3 H]-fucose by the salvage pathway (29,30). As shown in Figure 1, A and B, whereas the amount of radiolabeled fucose bound to acidprecipitable macromolecules was comparable in control, mother, and father, incorporation into macromolecules in patient cells was severely impaired (20% of that observed in the other samples).…”
Section: Resultsmentioning
confidence: 99%
“…Known C-1 phosphorylating enzymes are limited to mainly three types ( Fig. 2): the glycogen phosphorylases (16), which convert glycogen (9) into D-glucose-1-phosphate (10); fucokinases, which transfer a phosphate from ATP to the anomeric position of L-fucose (12) to provide ␤-L-fucose-1-phosphate (13) (17); and the galactokinases (GalK), which catalyze the formation of ␣-D-galactose-1-phosphate (Gal-1-P, 15) from D-galactose (14) and ATP. Previous studies have revealed that GalK from various sources have a limited substrate scope (18)(19)(20)(21), and in all C-1 kinases studied thus far, a strict adherence to either D-sugars (GalK and glycogen phosphorylases) or L-sugars (as in fucokinase) was observed.…”
mentioning
confidence: 99%
“…15. The divalent cations were also necessary for the GDP-L-Fuc pyrophosphorylase activity of rAtFKGP (Table 2).…”
Section: Identification Of Bifunctional L-fucokinase/gdp-l-fucosementioning
confidence: 99%
“…The specific activity of rAtFKGP for L-fucokinase was estimated at 0.17 unit/mg protein and that for GDP-L-Fuc pyrophosphorylase at 0.71 unit/mg protein (here the protein content was assessed based on the color intensity of rAtFKGP stained with Coomassie Brilliant Blue R-250 on SDS-PAGE). The specific activities of rAtFKGP apparently differ from those (1.27 and 0.36 units/mg protein, respectively) of pig L-fucokinase (15) and GDP-L-Fuc pyrophosphorylase (18). As has been observed for many nucleotide sugar pyrophosphorylases from other sources, rAtFKGP catalyzed both synthesis of GDP-L-Fuc from L-Fuc-1-P and GTP (GTP:L-fucose-1-phosphate guanylyltransferase action, the forward direction), and pyrophosphorolysis producing L-Fuc-1-P and GTP from GDP-L-Fuc and PP i (GDP-L-Fuc pyrophosphorylase action, the reverse).…”
Section: Identification Of Bifunctional L-fucokinase/gdp-l-fucosementioning
confidence: 99%
See 1 more Smart Citation